First names and social distinction: Middle-class naming practices in Australia. (September 2017) - Lindsay, Jo; Dempsey, Deborah
Naming practices provide a novel way to explore contemporary gender and class processes in Australia. Names are important everyday symbols of social location and signify family history, gender, class, ethnicity and religion. In an individualised society a name is the ultimate personal 'brand' and is used to locate children in social space. In this article we draw on qualitative interviews with 41 parents to focus on class and gender distinctions in naming practices. Naming a child was considered to be an important responsibility and names were viewed as central to identity and social classification. Through our exploration of naming preferences and judgements by middle-class parents, contemporary processes of social distinction come to light. Discussion of name choices illustrated parental aspirations and fears and the drawing of symbolic class-, gender- and sexuality-based cultural boundaries in Australia.